Pattern of cryospheric seismic events observed at Ekström Ice Shelf, Antarctica. Issue 10 (21st May 2015) - Hammer, Conny; Ohrnberger, Matthias; Schlindwein, Vera
Abstract Mobility of glaciers such as rapid retreat or disintegration of large ice volumes produces a large variety of different seismic signals. Thus, evaluating cryospheric seismic events (e.g., changes of their occurrence in space and time) allows to monitor glacier dynamics. We analyze a 1 year data span recorded at the Neumayer seismic network in Antarctica. Events are automatically recognized using hidden Markov models. In this study we focused on a specific event type occurring close to the grounding line of the Ekström ice shelf. Observed waveform characteristics are consistent with an initial fracturing followed by the resonance of a water‐filled cavity resulting in a so‐called hybrid event. The number of events detected strongly correlates with dominant tide periods. We assume the cracking to be driven by existing glacier stresses trough bending. Voids are then filled by seawater, exciting the observed resonance. In agreement with this model, events occur almost exclusively during rising tides where cavities are opened at the bottom of the glacier, i.e., at the sea/ice interface.